Вплив сполук кремнію на розподіл асимілятів у рослинах троянд, уражених Sphaerotheca pannosa Lev. var. rosea Woron. - Zaimenko, N.V.; Medin, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
It has been established the effect of the silicon to development of Sphaerotheca pannosa Lev. var. rosea Woron. It has been proved the rationality to use the silicon for activate physical and biochemical process in plants, to improve its adaptive ability to infact of powder mildew.